Collagen/hydroxyapatite composite materials: a regenerative platform versus drug delivery system - FICAI, Denisa; ALBU, Madalina Georgiana; CRISTESCU, Ioan; FICAI, Anton; ANDRONESCU, Ecaterina (Acta et Commentationes Exact and Natural Sciences, 2020)
The current review is intending to highlight the main advances in the field of collagen/hydroxyapatite (COLL/HA) composite materials as regenerative supports in bone tissue engineering but also as a platform for the delivery of different biological active agents with curative application. Basically, the review will highlight the most important synthesis routes as well as parameters able to tailor the characteristics of the COLL/HA composite materials as well as the most important achievements in the field of drug delivery systems based on COLL/HA using various classes of biologically active agents with different activity.